Remote Transplantation of Mesenchymal Stem Cells Protects the Heart Against Ischemia‐Reperfusion Injury. (15th July 2014) - Preda, Mihai Bogdan; Rønningen, Torunn; Burlacu, Alexandrina; Simionescu, Maya; Moskaug, Jan Øivind; Valen, Guro
Abstract : Cardioprotection can be evoked through extracardiac approaches. This prompted us to investigate whether remote transplantation of stem cells confers protection of the heart against ischemic injury. The cardioprotective effect of subcutaneous transplantation of naïve versus heme oxygenase‐1 (HMOX‐1)‐overexpressing mouse mesenchymal stem cells (MSC) to mice was investigated in hearts subjected to ischemia‐reperfusion in a Langendorff perfusion system. Mice were transplanted into the interscapular region with naïve or HMOX‐1 transfected MSC isolated from transgenic luciferase reporter mice and compared to sham‐treated animals. The fate of transplanted cells was followed by in vivo bioluminescence imaging, revealing that MSC proliferated, but did not migrate detectably from the injection site. Ex vivo analysis of the hearts showed that remote transplantation of mouse adipose‐derived MSC (mASC) resulted in smaller infarcts and improved cardiac function after ischemia‐reperfusion compared to sham‐treated mice. Although HMOX‐1 overexpression conferred cytoprotective effects on mASC against oxidative stress in vitro, no additive beneficial effect of HMOX‐1 transfection was noted on the ischemic heart. Subcutaneous transplantation of MSC also improved left ventricular function when transplanted in vivo after myocardial infarction. Plasma analysis and gene expression profile of naïve‐ and HMOX‐1‐mASC after transplantation pointed toward pentraxin 3 as a possible factor involved in the remote cardioprotective effect of mASC. These results have significant implications for understanding the behavior of stem cells after transplantation and development of safe and noninvasive cellular therapies with clinical applications. Remote transplantation of MSC can be considered as an alternative procedure to induce cardioprotection. Stem Cells 2014;32:2123–2134